Cochlear Implantation Under Local Anesthesia With Conscious Sedation in the Elderly: First 100 Cases. (14th July 2020) - Connors, Joseph R.; Deep, Nicholas L.; Huncke, T. Kate; Roland, J. Thomas
Abstract : Objective: To report the outcomes on a large series of elderly patients who underwent cochlear implantation (CI) surgery under local anesthesia with conscious sedation (LA‐CS). Methods: Retrospective chart review on 100 consecutive elderly patients (> 65 years) who underwent CI with LA‐CS at a tertiary care center between August 2013 and January 2020. An age‐matched control group of 50 patients who underwent CI with general anesthesia (GA) are used for comparison. Outcomes measured included time in the operating room, time in the postanesthesia care unit (PACU), and rate of adverse events. Results: Cochlear implant surgery under LA‐CS was successfully performed in 99 (99%) patients. One patient requiring conversion to GA intraoperatively. No patients in the LA‐CS group experienced cardiopulmonary adverse events; however, three patients (6%) in the GA group experienced minor events including atrial fibrillation and/or demand ischemia. Overnight observation in the hospital due to postoperative medical concerns or prolonged wake‐up from anesthesia was required in one patient (1%) from the LA‐CS cohort and 12 patients (24%) from the GA cohort. Perioperative adverse events exclusive to the LA‐CS group included severe intraoperative vertigo (8%), temporary facial nerve paresis (3%), and wound infection (1%). The average amount of time spent in the operating room was 37 minutes less for procedures performed under LA‐CS compared to GA ( P < .05). The average amount of time in recovery was similar for both groups ( P > .05). Conclusion: Cochlear implant surgery under LA‐CS offers many benefits and is a safe, feasible, and cost‐effective alternative to GA when performed by experienced CI surgeons. Level of Evidence: 3 Laryngoscope, 131:E946–E951, 2021